Classic and Golli Myelin Basic Protein have distinct developmental trajectories in human visual cortex - Siu, Caitlin R.; Balsor, Justin L.; Jones, David G.; Murphy, Kathryn M. (Frontiers in Neuroscience, 2015)
Traditionally myelin is viewed as insulation around axons however more recent studies have shown it plays an important role in plasticity, axonal metabolism and neuroimmune signalling. Myelin is a complex multi-protein structure composed of hundreds of proteins, with Myelin Basic Protein (MBP) being the most studied. MBP has two families: Classic-MBP that is necessary for activity driven compaction of myelin around axons, and Golli-MBP that is found in neurons, oligodendrocytes, and T cells, and has been called a 'molecular link' between the nervous and immune systems. In visual cortex myelin proteins interact with immune processes to affect experience-dependent plasticity. We studied myelin in human visual cortex using Western blotting to quantify Classic- and Golli-MBP expression in post-mortem tissue samples ranging in age from 20 days to 80 years. We found that Classic- and Golli-MBP have different patterns of change across the lifespan: Classic-MBP gradually increases to 42 years and then declines into aging; Golli-MBP has changes that are coincident with milestones in visual system sensitive period, before gradually increasing into aging. There are 3 stages in the balance between Classic- and Golli-MBP expression, with Golli-MBP dominating early, then shifting to Classic-MBP, and back to Golli-MBP in aging. Also Golli-MBP has a wave of high inter-individual variability during childhood. These results about cortical MBP expression are timely because they compliment recent advances in MRI techniques that produce high resolution maps of cortical myelin in normal and diseased brain. In addition the unique pattern of Golli-MBP expression across the lifespan suggests that it supports high levels of neuroimmune interaction in cortical development and in aging.